The hydro transport's rate and parameters of the lateritic mineral applied in the Moa Nickel S.A. Company, Holguin, Cuba - Izquierdo-Pupo, Raúl (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2007)
Here are exposed the installations fundamental parameters of the crude pulp hydro transit in the Moa Niquel S.A., plant.  This paper contains the results of an investigation over the lateritic pulp hydro transit that was realized in order to design and to exploit the installations of the hydro transit lateritic minerals witjh a sound techniche and economics.  The experimental research had as stage the industrial installations in expoitation and one semi-industrial installation, designed and buitt in I.S.M.M. According the experimental information the lateritic pulp has three types of movements: structural, transitory and turbulent.